IMPLEMENTASI PEMBERDAYAAN WANITA DALAM UPAYA MEWUJUDKAN KESEJAHTERAAN ANGGOTA KWT KEMIRI EDUM - Jhihan; Artita Devi Maharani; Avivah Rahmaningtyas (JURNAL ILMIAH AGRITAS, 2024)
This research aims to describe the process of empowering women through KWT, knowing the results of planning, implementation and evaluation in empowering women in KWT Kemiri Edum. This research uses basic qualitative research methods using a case study qualitative research type (case study) which is an in-depth research method of individuals, groups, organizations, activity plans at the Kemiri Edum KWT. The informants in this research involved 23 members of KWT Kemiri Edum as key informants, 4 daily administrators of KWT Kemiri Edum as supporting informants and UPTD BP4 Region 5 Pakem as additional informants totaling 2 people. The research results show that the women's empowerment program process for KWT Kemiri Edum members is going well, starting from the planning process, implementation to evaluation. Through the women's empowerment program, the welfare level of KWT Kemiri Edum members is at the Prosperous Family (KS) II and KS III stages based on the 2021 BKKBN regulations. Keywords: Women's Empowerment, KWT, Prosperity